ADAPTASI PASIEN PENYAKIT GINJAL KRONIK PADA EFEKTOR KONSEP DIRI : A LITERATURE REVIEW - Nana Rosliana; Titih Huriah (Jurnal EDUNursing, 2019)
ABSTRACTBackground: Treatment in patients with chronic kidney disease (CKD) will not change the natural course of kidney disease and will not restore all kidney function, resulting in problems and complications in physical and psychosocial conditions. Roy in his adaptation theory said that the problem in CKD patients was a reduction in adaptation to the effector of the self concept. If this problem is not addressed, it will cause new problems such as the low quality of life for CKD patients. Objective: Reviewing the journal on adaptation of self concept effector in CKD patients. Method: This study is a review literature study that focuses on the results of writing related to the self concept through searching accredited journal sites such as ProQoest, Ebsco, Scientdirect, Google Scholar, Clinical Key, Cochrane Library with keywords chronic kidney disease or chronic renal failure , adaptation, self concept and body image in the period 2013-2018 Results: Obtained 671 journals were identified based on keyword, then filtered based on inclusion criteria so that the total number of articles eligible for review was 8 journals. From the journal, reporting that 5 journals revealed about the physical self aspects which consisted of body image and body sensation. Conclusion: changes in self-concept adaptation to the physical self in patients with CKD that describe adaptation in the face of chronic disease. Keywords: Chronic Kidney Disease (CKD), adaptation, self concept